Differentiation of the plant cover on slopes of the Noteć valley near Ślesin (northern Poland) - Waldon, Barbara; Ratyńska, Halina; Boratyński, Adam (Biodiversity: Research and Conservation, 2006)
The south-facing slopes of the Noteć river valley near Ślesin are known as a refuge of xerothermic steppe species, relicts of the early Holocene. Part of the area is protected as the Nature Reserve “Skarpy Ślesińskie”. Floristic and phytosociological investigations of the plant complexes of the xerothermic grasslands, meadows, pastures and groves were carried out on the slopes between Ślesin and Trzeciewnica, including the nature reserve. In 25 plant complexes, 314 vascular plant species and 48 plant communities are found. The plant complexes of xerothermic grasslands are the richest floristically, while the meadows and pastures are the poorest. Spontaneous plants dominate in all units of plant landscape, reaching 80% of species, and more than half of plant communities are natural, almost exclusively auxochoric (i.e. composed of native species but occupying mainly anthropogenic sites). Adonis vernalis, Anemone sylvestris, Asperula tinctoria, Campanula sibirica, Gentiana cruciata, Potentilla rupestris, Scorzonera purpurea, Stachys recta, Stipa joannis, and Vicia tenuifolia, are the most noteworthy and protected plant species. They enter into well-developed, but small patches of Scorzonero purpureae-Stipetum joannis and Adonido-Brachypodietum. The communities deserve special protection and conservation.